Dietary and sex-specific factors regulate hypothalamic neurogenesis in young adult mice - Lee, Daniel A.; Yoo, Sooyeon; Pak, Thomas; Salvatierra, Juan; Velarde, Esteban; Aja, Susan; Blackshaw, Seth (Frontiers in Neuroscience, 2014)
The hypothalamus is the central regulator of a broad range of homeostatic and instinctive physiological processes, such as the sleep-wake cycle, food intake, and sexually dimorphic behaviors. These behaviors can be modified by various environmental and physiological cues, although the molecular and cellular mechanisms that mediate these effects remain poorly understood. Recently, it has become clear that both the juvenile and adult hypothalamus exhibit ongoing neurogenesis, which serve to modify homeostatic neural circuitry. In this report, we share new findings on the contributions of sex-specific and dietary factors to regulating neurogenesis in the hypothalamic mediobasal hypothalamus, a recently identified neurogenic niche. We report that high fat diet (HFD) selectively activates neurogenesis in the median eminence of young adult female but not male mice, and that focal irradiation of HFD-fed mice likewise reduces weight gain in females but not males. These findings suggest that the physiological effects of high fat diet may be mediated by the stimulation of neurogenesis in the hypothalamic median eminence in a sexually dimorphic manner. We discuss these results in the context of recent advances in understanding the cellular and molecular mechanisms that regulate neurogenesis in postnatal and adult hypothalamus.